Voltage gain and efficiency of a bi-layered radial mode piezoelectric/magnetoelectric solid-state transformer. Issue 174 (1st September 2016) - Montanher, D. Z.; Freitas, V. F.; Silva, D. M.; Gaiotto, F. J.; Pereira, J. R. D.; Cótica, L. F.; Santos, I. A.; Garcia, D.; Eiras, J. A.; Guo, R.; Bhalla, A. S.
ABSTRACT: Piezoelectric transformers are devices able to raise an electrical input voltage with low energy losses. However, there are a few reports on the designing of multiferroic piezoelectric transformers. In this paper, an alternative bi-layer radial mode piezoelectric/magnetoelectric transformer approach by using a Nb doped (1 wt%) Pb(Zr)53 Ti47 O3 piezoelectric ceramic as actuator, and a La doped (5 wt%) (0.6)BiFeO3 -(0.4)PbTiO3 magnetoelectric ceramic as transducer has been tested. The voltage gain and the efficiency were determined as a function of the frequency and the load test resistance. A typical response, characteristic of bi-layered radial mode solid-state transformer, with a voltage gain of 2.5 at a load resistance of 7 kΩ, and an efficiency of 0.15 at load resistance 1 kΩ, were obtained. The results showed the feasibility of such multiferroic transformer for some practical smart and multifunctional devices applications.